The The Analysis of Directorate-General of Tax Information System (SIDJP) Effectiveness to Improve the Employee Performance in 2021 (a Case Study at Pasar Rebo Small Tax Office) - Deni Malik; Nur Syabrina Lainun (Ilomata International Journal of Social Science, 2022)
Directorate-General of Tax (DJP) consistently reforms its tax administration system, among others by upgrading the Directorate-General of Tax Information System (SIDPJ) application to improve the previous application and therefore enable the tax officers for more efficient and effective work. The research aims to analyze the effectiveness of the Directorate-General of Tax Information System (SIDJP) to improve employee performance in 2021 (A Case Study at the Pasar Rebo Small Tax Office). The method used in the research was qualitative-descriptive using interviews, observation, and documentation to collect the data. The result of the research on the effectiveness of the SIDJP application shows that it has been effective in improving employee performance, as evidenced by the result of the interviews where employees find that they were facilitated in performing tax administration particularly tax administration and monitoring. However, the facts on the ground show that there were problems with the speed of access and occasional offline/downtime. Therefore, the recommended input for the system is to upgrade the SIDJP application with a more modern display and user-friendly layout to increase the storage and upgrade the server and bandwidth for faster data sending and receiving.